Analisis Penerapan Manajemen Risiko Dalam Penyaluran Pembiayaan Mikro (Studi Kasus Bank Syariah Indonesia KC Padang Imam Bonjol) - Fajar, Taufik M.; Dewi, Yenty Astarie (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study is to examine how risk management is used at the Bank Syariah Indonesia Padang Imam Bonjol Branch Office when distributing microfinance. Field research techniques are used in this study, which takes a descriptive qualitative approach. Through documentation, interviews, and observation, data was gathered. The findings of the study demonstrate that risk management has been correctly implemented in the distribution of microfinance at BSI KC Padang Imam Bonjol, taking into consideration the terms and conditions for potential users of microfinance. Furthermore, BSI KC Padang Imam Bonjol oversees the management of legal, market, finance, and strategic risks. To identify hazards in the distribution of microloans, the 5C principle, character, capacity, capital, collateral, and condition of economy is used.